PROTOTIPE SISTEM PENGAMAN PERLINTASAN KERETA API BERBASIS TEKNOLOGI SENSOR DAN KOMUNIKASI NIRKABEL - Kartika, Shendy; Dali Purwanto, Timur (Ensiklopedia of Journal, 2024)
Technology plays a very important role in human life, one of which is to support life. Many advanced technologies help humans improve the economy, food and computers. This progress has resulted in many tools that work automatically, in other words, operate without human commands in carrying out their functions and reduce human error. Especially in the field of transportation technology, such as the existing railway railroad piling barrier system that exists today still utilizes operator energy or still utilizes human energy. As a result, operator errors or failure to operate the checkpoints can result in accidents as sophisticated technology is now able to create safety systems for railroad crossings automatically. The research method used uses observation methods, interview methods, and literature study methods. The result of this research is that this prototype is able to make crossing gates open and close automatically. The way this system works is that there is a ultrasonic sensor that can detect the arrival or departure of a train and uses a lora module as a data sender or receiver which can make a servo motor or door latch driver open automatically. In calculations and measurements, this tool functions well because the error percentage in this system is below 5%.Keywords: Technology; Railway Doorstop; Ultrasonic sensor; LoRa moduls; Human error.